An Oxygenated Layer Coating to Enhance the Healing Process of Non-Healing Wounds—A Case Report - Tomasz Miłek; Anna Grzeczkowicz; Agata Lipko; Maria Mesjasz; Leszek Oklesiński; Angelika Kwiatkowska; Marcin Strawski; Monika Drabik; Ludomira H. Granicka (Applied Sciences)
The ever-increasing problem of chronic, non-healing wound treatment is a challenge in contemporary medicine. This study aims to verify the effect of a designed dressing containing a coating involving oxygenating factors on the promotion of wound healing in all healing phases in a single clinical case. An alginate-based coating, which incorporates the oxygenating factor, was produced. The obtained surface physicochemical features were examined using FTIR and AFM. The bandage support was modified with the developed coating and applied to patients who suffered from chronic wounds (treated with non-modified commercially available bandages) and had required treatment at least 3 months before starting the study. During bandage application, the chosen characteristics of the wound-healing process were examined. A histological evaluation of granulation tissue confirmed the presence of fibroblasts, hemorrhage, and lymphocytes during the second week of treatment. Moreover, epithelization tissue in the third week of treatment exhibited the presence of keratinocytes. A 100% wound reduction was observed between 3 and 4 weeks of treatment with the modified dressing. It can be recommended that the applied coating, which provides a supportive effect through oxygenating elements, inducing the remodeling phase in up to 4 weeks of treatment, be developed for use in hard-to-heal wound treatment.